In situ strategy for biomedical target localization via nanogold nucleation and secondary growth - Akira Sawaguchi (Nature Portfolio, 2021)
Sawaguchi et al. introduce a novel immunocytochemistry method that utilizes in situ gold nanoparticle labelling in immunoenzymatic products on universal paraffin/cryostat sections. The method is helpful, not only in overcoming limitations of the conventional nano gold labelling methods, but also useful in bridging the gap between light and electron microscopy.